B.02 Long-term neurodevelopmental outcomes in preterm twins. (June 2019) - Christensen, R; Chau, V; Synnes, A; Grunau, R; Miller, S
Abstract : Background: Preterm infants are at risk for adverse neurodevelopmental outcomes, however studies examining preterm twins are limited. The aim of this study was to examine whether preterm monozygotic (MZ) and dizygotic (DZ) twins have similar morbidities and long-term neurodevelopmental outcomes. Methods: From a cohort of 225 preterm neonates studied with MRI, 24 MZ and 52 DZ twins were included. Outcomes at 1.5-years, 3-years and 4.5-years were assessed with the Bayley-III, Movement Assessment Battery for Children and Wechsler Preschool and Primary Scale of Intelligence. Results: Twin pairs had substantial concordance for retinopathy of prematurity but only moderate-fair concordance for bronchopulmonary dysplasia, infection and brain injury. Differences in cognitive and language scores were stable over time, while motor differences increased. Discordant twins had significantly lower gestational age [Mean1(SD)=26.7(1.38); Mean2(SD)=29.1(2.1); P<0.001] and birth weight [Mean1(SD)=892.2(291.2); Mean2(SD)=1208.0(289.4); P=0.001] and a higher incidence of bronchopulmonary dysplasia and retinopathy of prematurity. In discordant twins, cognitive and language score differences decreased over time while motor differences increased. Conclusions: Preterm twin pairs have similar neurodevelopmental outcomes through early childhood despite poor concordance for perinatal illness. Discordant twins were born earlier and had more morbidities. Increasing concordance in cognitive and language outcomes over time may reflect the positive impact of early intervention programs.